Penggunaan bahan penguat fiber dan metal pada landasan gigi tiruan akrilik - Mira Andriani; Rasmi Rikmasari; Zulia Hasratiningsih (Jurnal Material Kedokteran Gigi, 2012)
Polymethyl methacrylate (PMMA /acrylic) has beenused extensivelyfor many yearsasthe maincomponent of denturebases. Clinical problemscommonly seen in the acrylic dentureis usually afractureat the midline. This occursdue toheavyocclusal forcesoracci dental damagesuch asfalling down while brushing the denture. Hence, it is necessary to strengthen the denture base especially the midline.The a forementioned issue can be solved by using reinforcement. Since those reasons above so that literature review will be presented on reinforcing materials ofacrylic denture. Denture base strengthening can be done using metal sandfibers. Each material has some advantages and disadvantages. The disadvantages of the metal reinforcement arein terms of aesthetics, can not chemically attached to the acrylic and can cause allergic reactions, furthermore, it is prone to corrosion. While the fiber reinforcement has aesthetics advantages due to its color and good adhesion to the acrylic. The addition of fiber or metalon the acrylic denture base can increase the strength of acrylic. The selection of a reinforcing material to be used should be considering the advantages and disadvantages of each material besides the availability in the dental laboratories.